The IBD6 Crohn's disease locus demonstrates complex interactions with CARD15 and IBD5 disease-associated variants. - van Heel, D; Dechairo, B; Dawson, G; McGovern, D; Negoro, K; Carey, A; Cardon, L; Mackay, I; Jewell, D; Lench, N (2003)
Genetic studies in inflammatory bowel disease have identified multiple susceptibility loci, whose relevance depends critically on verification in independent cohorts. Genetic variants associated with Crohn's disease have now been identified on chromosomes 5 (IBD5/5q31 risk haplotype) and 16 (IBD1 locus, CARD15/NOD2 mutations). Stratification of genome-wide linkage analyses by disease associated variants is now possible, offering both increased power for identification of other loci and improved understanding of genetic mechanisms. We performed a genome-wide scan of 137 Crohn's disease affected relative pairs from 112 families. Multipoint non-parametric linkage analyses were performed, with further stratification of affection status by common CARD15 mutations and the IBD5 haplotype. We verified linkage of Crohn's disease to regions on chromosome 3 (P=0.0009) and X (P=0.001) in our cohort. Linkage to chromosome 16 (IBD1) was observed in Crohn's disease pairs not possessing common CARD15 mutations (P=0.0007), approximately 25 cM q telomeric of CARD15. Evidence for linkage to chromosome 19 (IBD6) was observed in Crohn's disease pairs not possessing CARD15 mutations (P=0.0001), and in pairs possessing one or two copies of the IBD5 risk haplotype (P=0.0005), with significant evidence for genetic heterogeneity and epistasis, respectively. These analyses demonstrate the complex genetic basis to Crohn's disease, and show that the discovery of disease-causing variants may be used to aid identification of further susceptibility loci in complex disease.